Application and potential value of curcumin in prostate cancer: a meta-analysis based on animal models - Wang, Shiheng; Zhang, Fengxia; Chen, Jing (Frontiers in Pharmacology, 2024)
Introduction Curcumin is gaining recognition as an agent for cancer chemoprevention and is presently administered to humans. However, the limited number of clinical trials conducted for the treatment of prostate cancer is noteworthy. Animal models serve as valuable tools for enhancing our understanding of disease mechanisms and etiology in humans. The objective of this study was to examine the anti-prostate cancer effects of curcumin in vivo for comprehending its current research status and potential clinical applicability. Methods Our methodology involved a systematic exploration of animal studies pertaining to curcumin and prostate cancer, as documented in PubMed, Web of Science, Embase, Cochrane Library, CNKI, Wanfang database, Vip database, and SinoMed, up to 03 September 2023. Risk of bias was assessed using the SYRCLE Animal Study Risk of Bias tool. The results were combined using the RevMan 5.3. Results A comprehensive analysis was conducted on 17 studies encompassing 263 mouse transplantation tumor models. The findings of this meta-analysis demonstrated that curcumin exhibited a superior inhibitory effect on the volume of prostate cancer tumors in mice compared to the control group (standardized mean difference [SMD]: 1.16, 95% confidence interval [CI]: 0.52, 1.80, p < 0.001). Additionally, curcumin displayed a more effective inhibition of mice prostate cancer tumor weight (SMD: −3.27, 95% CI: −4.70, −1.83, p < 0.001). Furthermore, in terms of tumor inhibition rate, curcumin exhibited greater efficacy (SMD: 0.25, 95% CI: 0.23, 0.27, p < 0.001). Moreover, curcumin more effectively inhibited PCNA mRNA (SMD: −3.11, 95% CI: −4.60, −1.63, p < 0.001) and MMP2 mRNA (SMD: −3.19, 95% CI: 5.85, −0.53, p < 0.001). Conclusion Curcumin exhibited inhibitory properties towards prostate tumor growth and demonstrated a beneficial effect on prostate cancer treatment, thereby offering substantiation for further clinical investigations. It is important to acknowledge that the included animal studies exhibited considerable heterogeneity, primarily because of the limited number of studies included. Consequently, additional randomized controlled trials are required to comprehensively assess the efficacy of curcumin in humans. Systematic Review Registration (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023464661), identifier (CRD42023464661).